Erg6 gene is essential for stress adaptation in Kluyveromyces lactis - Konecna, Alexandra; Toth Hervay, Nora; Bencova, Alexandra; Morvova, Marcela; Sikurova, Libusa; Jancikova, Iva; Gaskova, Dana; Gbelska, Yvetta (FEMS microbiology letters, 2018)
We investigated the effect of Kluyveromyces lactis ERG6 gene deletion on plasma membrane function and showed increased susceptibility of mutant cells to salt stress, cationic drugs and weak organic acids. Contrary to Saccharomyces cerevisiae, Klerg6 mutant cells exhibited increased tolerance to tunicamycin. The content of cell wall polysacharides did not significantly vary between wild-type and mutant cells. Although the expression of the NAD+-dependent glycerol 3-phosphate dehydrogenase (KlGPD1) in the Klerg6 mutant cells was only half of that in the parental strain, it was induced in the presence of calcofluor white. Also, cells exposed to this drug accumulated glycerol. The absence of KlErg6p led to plasma membrane hyperpolarization but had no statistically significant influence on the plasma membrane fluidity. We propose that the phenotype of Klerg6 mutant cells to a large extent was a result of the reduced activity of specific plasma membrane proteins that require proper lipid composition for full activity.
Keywords: kationické antimikrobiální peptidy; Methyltransferases; fungální proteiny; Adaptation, Physiological; Carboxylic Acids; tolerance léku; Osmotic Pressure; kyseliny karboxylové; Antimicrobial Cationic Peptides; delece genu; Drug Tolerance; Gene Deletion; Kluyveromyces; osmotický tlak; fyziologická adaptace; methyltransferasy; regulace genové exprese u hub; Gene Expression Regulation, Fungal; Fungal Proteins